Predictors of In-Hospital Mortality in Patients with Acute Coronary Syndrome in Hasan Sadikin Hospital, Bandung, Indonesia: A Retrospective Cohort Study - Miftah Pramudyo; Achmad Fauzi Yahya; Erwan Martanto; Badai B Tiksnadi; Giky Karwiky; Raissa Rafidhinar; Gemi Nastiti Indi Putri (Acta Medica Indonesiana)
Background: Acute coronary syndrome (ACS) is a world health problem with a high mortality rate and is expected to continue to rise in number. The high ACS mortality rate in the hospital is influenced by demographic characteristics, cardiovascular risk factors, clinical presentation, and management. This study aimed to determine the predictors of ACS death at Dr. Hasan Sadikin Hospital Bandung as the highest referral center in West Java. Methods: This study is a retrospective cohort study on all ACS patients undergoing treatment at Dr. Hasan Sadikin Hospital Bandung from January 2018 to December 2019. Multivariate analysis was performed using a logistic regression test with the backward method to assess predictors of patient outcomes. Results: This study involved 919 patients with the in-hospital mortality rate was 10.6%. Multivariate analysis showed that age >65 years was a demographic factor that play a role as a predictor of mortality mortality (AOR 2.143; 95% CI = 1.079-4.256; p = 0.030). Clinical presentation of cardiac arrest arrest (AOR 48.700; 95% CI =14.289-165.980; p<0.001), SBP <90 mmHg (AOR: 4.972; 95% CI =1.730-14.293; p=0.003, heart rate >100 beats per minute (AOR 4.285; 95% CI =2.209-8.310; p<0,001), cardiogenic shock (AOR: 5.433; 95% CI= 2.257-13.074; p<0.001). Cardiovascular management can reduce the risk of in-hospital mortality. Multivariate analysis showed statins (AOR 0.155; 95% CI=0.040-0.594; p=0.007), beta blockers (AOR 0.304; 95% CI=0.162-0.570; p<0,001) and Percutaneous Coronary Intervention (AOR 0.352; 95% CI=0.184-0.673; p=0.002) significantly reduce in-hospital mortality. Interestingly, smoking is associated with a lower mortality rate (OR 0.387; p <0.001). Conclusion: Clinical presentation of cardiac arrest has the highest risk of death, the sequence is cardiogenic shock, heart rate >100 beats per minute, and age >65 years. Administration of statins, beta-blockers, PCI, and smoking are factors that reduce the risk of death.